Rancière and Emancipatory Art Pedagogies The Politics of Childhood Art - Park, Hayon (Radical Politics and Education, 2022)
Drawing on the thoughts of Jacques Rancière, this open access book seeks to understand the politics of childhood art by attending to the relational matters in children's artistic practices rather than the linear age-based developmental theories which often limit children's creativity. Weaving Rancière's ideas on pedagogy, politics, and aesthetics, with a research study at a Kindergarten classroom in the USA and the author's own art experiences in South Korea as a child, Hayon Park discusses the politics and ethics of teacher-led art projects, children's popular culture, and adult-child drawing companionship. The author argues that childhood art and in education is inherently political and relational as, from an early age, children are acutely aware of monitoring, categorisation, and the potential oppression of their art making and learning. Offering a post-structural, reconceptualist approach to art education, Park argues for new emancipatory practices and pedagogies, which encourage children's creativity and activate curiosity. The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.